International R&D spillovers in transition countries: the impact of trade and foreign direct investment - Marius Sorin Krammer (Kiel Institute for the World Economy (IfW), 2008)
While the economic theory predicts that developing countries will gain the most from technology spillovers, there have been only a few analyses looking at this question empirically. The present study focuses on a panel of 27 transition and 20 Western European countries between 1990 and 2006 and uses the latest developments in panel unit root and cointegration testing to disentangle the effects of international spillovers via trade and FDI. My findings show that imports remain the main channel of diffusion for both sets of countries, while FDI, although significant econometrically, has less quantitative impact on domestic productivity. The domestic R&D capital stock plays an active role in Western Europe while in the Eastern part is much less important. Human capital has an overall robust positive influence on TFP. The results confirm that transition countries seem to gain more in terms of productivity from the international diffusion process than their Western counterparts.
Keywords: O30; O47; O57; C23; D24; 330; Technology spillovers; trade; investment; panel cointegration; Technischer Fortschritt; Transformationsstaaten; Innovationsdiffusion; Spillover-Effekt; Direktinvestition; Internationale Wirtschaftsbeziehungen; Panel; Kointegration; Schätzung; Welt